2016
DOI: 10.2196/jmir.5082
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and External Validity of Electronic and Mobile Phone-Based Interventions Promoting Vegetable Intake in Young Adults: Systematic Review and Meta-Analysis

Abstract: BackgroundYoung adults (18–35 years) remain among the lowest vegetable consumers in many western countries. The digital era offers opportunities to engage this age group in interventions in new and appealing ways.ObjectiveThis systematic review evaluated the efficacy and external validity of electronic (eHealth) and mobile phone (mHealth) -based interventions that promote vegetable intake in young adults.MethodsWe searched several electronic databases for studies published between 1990 and 2015, and 2 independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 75 publications
5
88
0
8
Order By: Relevance
“…[40][41][42][43] A recent review article by Nour and colleagues found that many studies that used mobile phone technology to increase vegetable consumption were effective. 44 We are unaware of any other FM studies that employ internet-based promotion tactics for increasing FM use among SNAP participants. Currently, there is no consensus on the effectiveness of app-based interventions on influencing dietary behaviors.…”
Section: Farmers' Market Utilization -Nuss Et Almentioning
confidence: 99%
“…[40][41][42][43] A recent review article by Nour and colleagues found that many studies that used mobile phone technology to increase vegetable consumption were effective. 44 We are unaware of any other FM studies that employ internet-based promotion tactics for increasing FM use among SNAP participants. Currently, there is no consensus on the effectiveness of app-based interventions on influencing dietary behaviors.…”
Section: Farmers' Market Utilization -Nuss Et Almentioning
confidence: 99%
“…Data recording of blood glucose and life-style changes has progressed from recording them in paper to uploading them to computers and using traditional phone functions, and finally to using smartphone apps. Many systematic reviews and meta-analyses proved that mHealth tools are effective in self-management in a wide range of areas both for disease-management and life-style changes in daily life [68]. Previous reviews of the mHealth tools have focused largely on text messaging, phone calls, or computer-based or laptop/tablet-based interventions rather than focusing on smartphone apps[9].…”
Section: Introductionmentioning
confidence: 99%
“…In particular there is limited information regarding the best application characteristics for disadvantaged populations (5). There have been a number of early systematic reviews that examine the efficacy of health application interventions; however, these either focus on weight loss rather than nutrition improvement (10)(11)(12)(13)(14), exclude qualitative and descriptive studies (15,16), and/or include text messaging and Web-based interventions (10,12,13,(16)(17)(18), with none specifically relating to community settings.…”
Section: Introductionmentioning
confidence: 99%